Prevalence and Characteristics of Computer Vision Syndrome Among Nursing Students in Online Learning Environments: A Cross-Sectional Study - Rizqi, Januar; Fitriawan, Akbar Satria (Universitas Nahdlatul Ulama Surabaya, 2025)
The increased use of digital devices in online learning poses health risks, one of which is Computer Vision Syndrome (CVS). Nursing students are among the vulnerable groups due to high visual load and long learning duration. This study aims to describe the symptoms of CVS in nursing students during online learning and evaluate the behaviour of using digital devices as a risk factor. The study used a quantitative descriptive design with a cross-sectional approach. A total of 399 nursing students from various universities in Indonesia participated through a total sampling technique. Data were collected online using a questionnaire based on the American Optometric Association guidelines, including demographic information, online learning behaviour, and CVS symptoms. The analysis was done descriptively with frequency distribution and percentage. The results showed that the majority of respondents experienced CVS symptoms in the mild to moderate category, such as headache (47.9% mild; 37.8% moderate), burning eyes (42% mild), and blurred vision (39.6% mild). Most students (62.9%) used smartphones and had been studying online for more than six months (94.9%). In conclusion, CVS is a common problem among nursing students in online learning. Educational and preventive interventions are needed to maintain students' visual health.